Determinants of Personal Hygiene Behavior in the Elderly at the Tresna Werdha Social Service Technical Implementing Unit Jember - Putri, Rosyta Dwi Untika; Ma’rufi, Isa; Rokhmah, Dewi Rokhmah (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: There was an increase in the number of elderly people by 8.1% in 2019 compared to 2018 (Indonesian Ministry of Health, 2019).  The increasing number of elderly people in Indonesia will cause health and welfare problems, especially related to personal hygienePurpose: This study aims to analyze the determinants of personal hygiene behavior in the elderly at UPT PSTW Jember by utilizing the ABCD concept (Asset Based Community Development which is also reviewed from the behavior of the elderly and assets owned by UPT Tresna Werdha Jember Social ServicesMethod: The design of this study was analytic observational with a population of 140 elderly people and a sample size of 58 elderly people taken using systematic smpling techniquesResult: The results showed that knowledge, attitudes, social assets, facilities and infrastructure and health information / training had an influence on personal hygiene behavior in the elderly at UPT PSTW Jember. The Odds Ratio value of 13.074 means that social assets have the opportunity to influence personal hygiene behavior 13.074 times compared to the variables of knowledge and infrastructureConclusion: The dominant factor that has the most influence on the personal hygiene behavior of the elderly at UPT PSTW Jember is social assets.